The Limpopo Magma‐Rich Transform Margin, South Mozambique: 1. Insights From Deep‐Structure Seismic Imaging. Issue 12 (9th December 2021) - Watremez, L.; Leroy, S.; d'Acremont, E.; Roche, V.; Evain, M.; Leprêtre, A.; Verrier, F.; Aslanian, D.; Dias, N.; Afilhado, A.; Schnürle, P.; Castilla, R.; et al.
Abstract: A variety of structures results from the interplay of evolving far‐field forces, plate kinematics, and magmatic activity during continental break‐up. The east Limpopo transform margin, offshore northern Mozambique, formed as Africa and Antarctica separated during the mid‐Jurassic period break‐up of the Gondwana supercontinent. The nature of the crust onshore has been discussed for decades in an effort to resolve issues with plate kinematic models. Two seismic refraction profiles with coincident multichannel seismic reflection profiles allow us to interpret the seismic velocity structures across the margin, both onshore and offshore. These seismic profiles allow us to (a) delineate the major regional crustal domains; (b) identify widespread indications of magmatic activity; and (c) map crustal structure and geometry of this magma‐rich transform margin. Careful examination of the profiles allows us to make the following observations and interpretations: (a) on land, continental crust is overlain by a >10‐km thick volcano‐sedimentary wedge related to an early rifting stage, (b) offshore, thick oceanic crust formed due to intense magmatic activity, and between the two (c) a 50–60‐km wide transform zone where the crustal structures are affected by intense magmatic activity and faulting. The prominent presence of intrusive and extrusive igneous units may be attributed to the combination of a deep‐seated melting anomaly and a trans‐tensional fault zone running through thinned lithosphere that allowed melt to reach the surface. A comparison of the crustal thinning along other transform margins shows a probable dependence with the thermal and/or tectonic history of the lithosphere. Key Points: New seismic velocity models across east Limpopo delineates crustal domains, from stretched continental crust to thick oceanic crust Intense magmatic activity associated with a mantle plume affected the entire margin during all stages of its formation Transform margin structure and geometry are controlled by structural inheritance, syn‐tectonic sedimentation, and magmatic activity history